Exploring regulatory systems of informal economic activity in a dense settlement: The case of Extension 2, Ivory Park, Johannesburg - Nzimande, Thabisani (University of the Witwatersrand, Johannesburg, 2024)
Informal economic activities are a crucial component of most economies in the global south. They are easily accessible as a tool for poverty alleviation and to fight against unemployment, due to easy entry requirements and no extensive processes to start a business. Home-based enterprises in particular offer a unique ability to minimise overheads and save on costs such as traveling expenses for business owners as economic activity occurs in the residential area. The growing number of home-based enterprises in housing settlements has made it impossible for the government to ignore them and has necessitated the need for government to recognise and regulate them. This study explores the regulatory systems of home-based enterprises in Ivory Park, Extension 2 on 29th September Drive. Ivory Park is a housing settlement located in Region A in the City of Johannesburg. The area of focus is a stretch of a busy street located in between the main taxi rank in Extension 2, and Busy Corner Mall making this one of the busiest streets in the settlement. The area hosts a number of home-based enterprises located on the side-lines of 29th September Drive such as hair salons, spaza shops, clothing shops, fast-food outlets, internet cafes/ printing shops, furniture shops, and carpentry, plus a number of traditional medicine shops. The main objective of this study is to ascertain what are the systems which seek to regulate and facilitate home-based enterprises/ informal economic activity in this area. The findings were made after consultation with literature, documents about the study area, and interviews with business owners, homeowners, a community leader, and a municipal official. This study revealed that the formal regulations set by the City of Johannesburg are largely informed by land use and planning development objectives and are very rigorous to adhere to by most homeowners and business owners. This combined with a lack of knowledge of the regulations has resulted in low levels of compliance, with most business owners relying on informal regulatory systems to manage their operations and affairs. Furthermore, this research report makes recommendations that programmes should be created to educate business owners and homeowners on the regulations which apply to them, and to revise the current regulations which seek to protect the integrity of planning and development objectives without any consideration for practicality for, and the economic development of the informal sector
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Home-based enterprises; informal economy; informal settlements; Land-use regulations; SDG-8: Decent work and economic growth